Synthesis of Triarylpyrylium Salts Using a Mild, Eco-friendly Route - Owen, Connor; Spiridopoulos, Casey; Starvaggi, Nicholas; Morrow, Zachary; Chirdon, Danielle; Mills, Isaac (Synlett, 2024)
Pyrylium salts based on a cationic oxygen heterocycle are a key class of chromophores. However, synthesis of these salts generally requires use of harsh acids, copious organic solvents, and in many cases, hazardous conditions. This work provides a two-pot synthesis for substituted triphenyl pyrylium salts wherein chalcone intermediates are first prepared and then mild methanesulfonic acid is used in combination with a dehydrating agent to drive pyrylium cyclization. Purification is achieved through a simple, aqueous workup involving counterion metathesis which avoids the need for environmentally unfriendly organic solvents. This mild, green approach has been applied to synthesize a collection of known pyryliums as well as a new family of red-shifted pyrylium chromophores bearing p-pyrrolidinylphenyl substituents. The synthesis of the latter group demonstrates that unlike other current methods, our approach offers enhanced functional group tolerance as well as finer control over substituent placement.
Keywords: photochemistry; green chemistry; condensation; chromophores; cyclization